The Role of the Family in Preventing Child Wasting: A Systematic Literature Review - Anto J. Hadi; Lucy Widasari; Hapiz Arlanda Sani; Erni Yetti R; Zadrak Tombeg; Saskiyanto Manggabarani (PT Yapindo Jaya Abadi, 2026)
ABSTRACT Wasting is one of the public health nutrition problems in developing countries including South Asia, Africa, and Indonesia. This condition can lead to an increased risk of death in children under five years of age and affect their physical and cognitive development. Research shows that in addition to nutritional factors, the role of the family, including parenting, feeding, and social support, plays a significant role in preventing and overcoming wasting in children. This systematic literature review aims to explore the role of families in wasting prevention in children, focusing on factors that may influence the incidence of wasting. This study used a systematic literature review (SLR) approach by searching for relevant articles from various academic databases such as scopus. The selected articles analyzed family factors that contribute to the occurrence of wasting in children, including the role of mothers, parental education, household economic status, and the role of social support. Data were collected from various surveys and studies in countries with high prevalence of wasting, including countries in South Asia and Africa. The results of the analysis showed that family factors such as the mother's education level, nutritional knowledge, good parenting, and access to health facilities played a significant role in the prevention of wasting in children. In addition, families with low socio-economic status and limited access to clean water and poor sanitation are more at risk of wasting events. Some effective family-based interventions include providing nutrition education to parents, supplemental feeding programs, and increased social support for high-risk families. The role of the family is very important in the prevention of wasting in children, especially through the improvement of parenting behavior and nutritious feeding. Wasting prevention programs need to actively involve families by providing nutrition education, as well as providing adequate social support and health facilities. Multisectoral interventions involving the health, sanitation, and education sectors must be strengthened to achieve more effective reduction in the prevalence of wasting. Keywords: prevention of wasting, role, family, children, social support, parenting behavior